2020
DOI: 10.11628/ksppe.2020.23.1.35
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Effectiveness of the Frequency and Duration of the Horticultural Therapy Program on Elderly Women with Mild Cognitive Impairment and Mild Dementia

Abstract: The purpose of this study was to investigate the effects of the horticultural therapy program on patients with mild cognitive impairment and mild dementia depending on the frequency and duration of the interventions. We developed the same 15-session program to improve cognitive functions and life satisfaction and alleviate depression of the elderly women with mild cognitive impairment or mild dementia. Subjects in Longer Treatment group participated in the program once a week for 15 weeks and subjects in Short… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…We yielded a total of 7,366 articles; we eliminated 2,794 articles due to duplication, 4.503 due to irrelevant titles and abstracts, and 57 articles due to the failure to meet the criteria or unavailable full text (e.g., not people aged 60 or above, not people with depression, or not horticultural therapy). Twelve articles reporting 13 studies were finally included in this meta-analysis since two studies were from the same article ( 48 ). Six of which were RCTs and seven were quasi-experimental studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We yielded a total of 7,366 articles; we eliminated 2,794 articles due to duplication, 4.503 due to irrelevant titles and abstracts, and 57 articles due to the failure to meet the criteria or unavailable full text (e.g., not people aged 60 or above, not people with depression, or not horticultural therapy). Twelve articles reporting 13 studies were finally included in this meta-analysis since two studies were from the same article ( 48 ). Six of which were RCTs and seven were quasi-experimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Chu et al ( 37 ) recruited 150 participants, and Wang and Jiang ( 49 ) recruited 126 participants, with six studies including < 30 participants. Nine studies had both male and female participants, while study from McCaffrey et al ( 50 ) did not describe the gender composition of the participants, and studies from Kim ( 48 ) and Szczepanska et al ( 51 ) had only female participants. All of the aged people involved in the studies had normal cognitive function, except for Kim ( 48 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…carried out in a short period of time. The total scores of depression before the program showed that both the experimental group(M = 38.50, SD = 11.75) and control group (M = 33.00, SD = 7.26) showed high depression in the range of 'Has depressive symptoms (22-60 points)'.According toSon et al (2006), long intervention periods are effective if the purpose is mental and psychological rehabilitation, andKim et al (2020) also mentioned that it was effective to apply at least 3-4 months of the program aimed at mental and psychological rehabilitation. However, this study was conducted in a relatively short period of time, twice a week for 4 weeks (about a month), which is not enough time alleviate the high level of depression among the participants.…”
mentioning
confidence: 99%